Responsiveness of Early Response to Dehydration Six-Like Transporter Genes to Water Deficit in Arabidopsis thaliana Leaves - Slawinski, Lucie; Israel, Abir; Artault, Caroline; Thibault, Florence; Atanassova, Rossitza; Laloi, Maryse; Dédaldéchamp, Fabienne (Frontiers in Plant Science, 2021)
Drought is one of the main abiotic stresses, which affects plant growth, development and crop yield. Plant response to drought implies carbon allocation to sink-organs and sugar partitioning between different cell compartments, and thereby requires the involvement of sugar transporters. Among them, the ESLs (Early-response-to-dehydration Six-Like), with 19 members in Arabidopsis thaliana, form the largest sub-family of monosaccharide transporters still poorly characterized. Common feature of these genes is their involvement in plant response to abiotic stresses including water deficit. In this context, we carried out morphological and physiological phenotyping of A. thaliana plants grown under well-watered and water-deprived conditions, together with expression profiling of seventeen AtESL genes in rosette leaves. The drought responsiveness of twelve ESL genes, four up-regulated and eight down-regulated, was correlated to different water status of the rosette leaves. The differential expression of each of the tandem duplicated AtESL genes in response to water stress argues in favor of their plausible functional diversity. Furthermore, T-DNA insertional mutants for each of the four up-regulated ESLs in response to water deprivation were identified and characterized under well-watered and water-deprived conditions. To gain insight into global sugar exchanges between vacuole and cytosol under water deficit, gene expression of other vacuolar sugar transporters and invertases (AtTMT, AtSUC, AtSWEET and AtFRUCT) was analyzed and discussed.